GURU PROFESIONAL DALAM KONSEP KURIKULUM 2013 - Fakhrul Rijal (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
Curriculum 2013 is the result of the developing education curriculum in Indonesia which was discharged on July 15, 2013 based on the philosophy foundation, the juridical foundation and empirical foundation. The special feature of curriculum 2013 is to demand the ability of teachers to be knowledgeable as much as possible, to master technology and information, to encourage students to have responsibility to the environment, to have interpersonal, between individuals, and critical thinking skills so that students become productive, creative, and innovative. The role of professional teachers as the main implementers of the curriculum 2013 should be developed in accordance with the curriculum requirements, such as: teachers must inspire / love their profession, experts in the field of science, mastering the way of interaction / communication, joining various professional organizations, able to use Various kinds of information technology, make innovations to the (materials, methods, media and tools) learning, and evaluate with three criteria of assessing the ability (cognitive, affective and Psychomotor) ability of each learner.